Influence of Solute Molecular Diameter on Permeability-Selectivity Tradeoff of Thin-Film Composite Polyamide Membranes in Aqueous Separations. (1st August 2021) - Chen, Xi; Boo, Chanhee; Yip, Ngai Yin
Highlights: Permeability-selectivity tradeoff slope is related to solute and solvent diameters Intercept of the tradeoff line is governed by solute size Underlying principles of solution-diffusion theory applies to polyamide membranes Identified new regime where solute and water transport rates are weakly dependent Abstract: Fundamental understanding of the reverse osmosis (RO) transport phenomena is necessary for quantitative prediction of contaminant rejection and development of more selective membranes. The solution-diffusion (S-D) model predicts a tradeoff relationship between permeability and selectivity, and this tradeoff trend was recently reported for RO. But the first principles governing the relationship are not well understood for aqueous separation membranes. This study presents a framework to elucidate the underlying factors of the permeability-selectivity tradeoff relationship in thin-film composite polyamide (TFC-PA) membranes. Water and solute permeabilities of membranes with a range of selectivities are examined using six nonelectrolyte solutes of various sizes and dimensions. The permeability-selectivity tradeoff trend, as defined by S-D, was observed for all six solutes. Crucially, the slopes of the tradeoff lines, λ, are found to be related to the solute and solvent (i.e., water) diameters, d s and d w, respectively, by λ = ( d s / d w ) 2 – 1, consistent with the S-D framework established for gas separation membranes. Additionally, the intercepts of the tradeoff lines are shown to be also influenced by d s . These results highlight that solute molecular diameter is a primary influence on the permeability-selectivity tradeoff for the permeants investigated in this study. Furthermore, a transport regime where solute permeation is only very weakly coupled to water transport, in addition to the conventional S-D, is identified for the first time. We demonstrate that the boundary delineating the two transport regimes can be determined by the solute diameter. The relationship between characteristic features of the "additional regime" and solute dimensions are analyzed. The study shows that the general principles of the S-D framework are applicable to TFC-PA membranes and the analysis quantified the principal role of solute size in governing RO transport. The experimental and analytical evidence suggest that nonelectrolyte solute transport can, in principle, be a priori predicted using molecular diameter. Findings of this investigation provide new insights for understanding the transport mechanisms in osmotic membrane processes.